A DIAGNOSTIC DILEMMA: RECURRENT HYPOKALEMIC WEAKNESS SECONDARY TO SJOGREN'S SYNDROME (A DRTA EFFECT) - KARPATIYA, MAULIK KUMAR; RATHWA, SANJAYKUMAR; SHAH, PRAYANS; RATHWA, PRATIKSHA (International Journal of Current Pharmaceutical Research, 2025)
Renal involvement occurs in approximately 5% of patients with Sjogren’s syndrome (SS). Renal lesions that predominate are tubulointerstitial nephritis and membranoproliferative glomerulonephritis. We report the case of a 50-year-old female who presented with weakness of lower limbs. A diagnosis of distal renal tubular acidosis type 1 (DTA1) secondary to SS was made, discovered in view of hypokalemic paralysis. The patient was treated symptomatically with injectable potassium chloride sodium bicarbonate. Corticosteroid and hydroxychloroquine were used to treat SS. The patient improved with correction of acidosis and hypokalemia.